Foliar spray of seaweed extract and fertilizers on sweet pepper (Capsicum annuum) (UNED Research Journal, 2022)
Introduction: Seaweed extracts have biostimulant activities that improve growth and yield in many crops, and can improve mineral absorption. Objective: to evaluate the effects of foliar spray of seaweed extract and fertilizers (treatments:  seaweed extract (SE); fertilizers (FF); seaweed extract+fertilizers (SE+FF); and control-C) on the yield and quality of sweet pepper grown under greenhouse conditions. Methods: The crop was managed in a coconut fiber substrate and with fertigation. Evaluated variables were:  number of fruits per plant, fruit weight (g), yield (ton/ha), percentage of total soluble solids (°Brix), chlorophyll content (atLEAF), leaf area (cm2), leaf dry weight (g), specific leaf weight (mg/cm2), plant height (cm), and stem diameter (mm). Treatments were applied from 14 days after transplant (ddt), and were carried out weekly until the end of the trial (154 ddt). Results: Treatments SE and SE+FF produced a higher number of commercial and total fruits per plant, as well as higher commercial and total yields when compared to treatments FF and C. The SE+FF treatment produced a greater fruit weight, compared to treatment C, both at a commercial and total level. No significant differences between treatments were observed for the following variables:  leaf area, leaf dry weight, leaf specific weight, plant height and stem diameter. Conclusion: The use of the seaweed extract (SE) produced the highest total and commercial yield at the lowest cost, and thus its utilization is recommended under the trial conditions; on the other hand, the application of foliar fertilizers (FF) under the same conditions did not improve neither the yield of sweet peppers nor their quality.
Keywords: Keywords: stress, physiology, nutrition, production, hydroponics